META-ANALISIS : Pengembangan Lembar Kerja Peserta Didik Berbasis STEAM Untuk Peserta Didik - Dwi Maharani , Angela; Zulyusri (INSTITUT AGAMA ISLAM NEGERI AMBON, 2024)
The 21st century that the world has entered is known as the century of globalization or openness which requires high quality human resources who have knowledge in the fields of technology and information management, learning and creativity, as well as building independence. The STEAM (Science, Technology, Engineering, Art, and Mathematics) learning approach is an approach that can adapt to the characteristics of 21st Century learning. Student guides called LKPD are used for research and problem solving exercises. This meta-analysis based research is useful for determining the feasibility of STEAM-based Student Worksheets in learning. The method used in this research is meta-analysis, namely by summarizing the results of different studies and re-analyzing existing research. The articles used were published between 2020-2024. The results obtained show that the STEAM-based Student Worksheet is suitable for use in learning. Keywords: Meta-analysis, Leaner Worksheets, STEAM